2021
DOI: 10.1093/toxsci/kfab122
|View full text |Cite
|
Sign up to set email alerts
|

Blood Neurofilament Light Chain as a Potential Biomarker for Central and Peripheral Nervous Toxicity in Rats

Abstract: Neurotoxicity is a principal concern in nonclinical drug development. However, standardized and universally accepted fluid biomarkers for evaluating neurotoxicity are lacking. Increasing clinical evidence supports the potential use of neurofilament light chain (NfL) as a biomarker of several neurodegenerative diseases; therefore, we investigated changes in the cerebrospinal fluid (CSF) and serum levels of NfL in SD rats treated with central nervous system (CNS) toxicants [trimethyltin (TMT, 10 mg/kg p.o., sing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 38 publications
(60 reference statements)
2
13
0
Order By: Relevance
“…However, these studies lacked a comparison of peripheral nerve damage, including DRG lesions, to CSF NfL levels, especially from the perspective of the effects of DRG lesions on NfL levels. Conversely, we previously reported that a pyridoxine-induced sensory neuropathy model showed DRG and peripheral nerve changes, with apparent increased NfL levels in both the serum and CSF 5 . NfL is abundant in the axon and DRG 7,8 , and the DRG and its surrounding nerve fibers potentially communicate directly with the CSF in the subarachnoid space in rats 9 .…”
mentioning
confidence: 69%
“…However, these studies lacked a comparison of peripheral nerve damage, including DRG lesions, to CSF NfL levels, especially from the perspective of the effects of DRG lesions on NfL levels. Conversely, we previously reported that a pyridoxine-induced sensory neuropathy model showed DRG and peripheral nerve changes, with apparent increased NfL levels in both the serum and CSF 5 . NfL is abundant in the axon and DRG 7,8 , and the DRG and its surrounding nerve fibers potentially communicate directly with the CSF in the subarachnoid space in rats 9 .…”
mentioning
confidence: 69%
“…However, previous studies report increased NF-L in rats treated with various neurotoxicants (e.g., chloropropionic acid, acrylamide, trimethyltin, kainic acid), as well as rodent models of Huntington’s disease and pneumococcal meningitis. 33 , 34 , 35 , 36 Moreover, circulating NF-L was elevated in patients with traumatic brain injury (TBI) 37 , 38 , 39 and several neurodegenerative diseases including multiple sclerosis, Alzheimer’s disease, ALS, spinal muscular atrophy, and Guillain-Barré syndrome. 40 , 41 , 42 , 43 In each of these studies, NF-L was elevated in CSF as well as blood-derived biofluids.…”
Section: Discussionmentioning
confidence: 99%
“…The efficacy of serum NFL as a biomarker of neuroaxonal damage emerged initially in multiple sclerosis, where it serves for prognosis and treatment monitoring [ 10 , 11 ]. Currently, there is growing scientific evidence associating serum NFL with other neurodegenerative diseases [ 12 ] and peripheral neuropathies in humans [ 13 25 ] and animals [ 26 28 ]. However, evidence of a potential association between NFL and DSPN is scarce.…”
Section: Introductionmentioning
confidence: 99%